2020
DOI: 10.3390/nu12103170
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Neural Tube Defects by Folic Acid Supplementation: A National Population-Based Study

Abstract: Folic acid supplementation is recommended for neural tube defect prevention during pregnancy. We conducted an observational, retrospective national registry study to determine the rate of dispensing of periconceptional folic acid after prescription in a sample of French women representative of the general population. Our study population (n = 186,061) was a representative sample of the French population, recorded in the Health Data System database on pharmacy dispensing of medication and mandatory reporting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…Only 17% of the >22,000 respondents were aware that folic acid reduces the risk of NTDs and only 28% of those women currently trying to become pregnant were taking folic acid supplements [9]. A recent study from France revealed that only 6.4% of women filled their prescription for folate supplements in the preconceptional period between 2006 and 2016, based on objective data from registries [39]. Even though over-the-counter supplements were not included, this low number may indicate that self-reported adherence to supplement recommendations, as used in most other studies, might be overestimated to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Only 17% of the >22,000 respondents were aware that folic acid reduces the risk of NTDs and only 28% of those women currently trying to become pregnant were taking folic acid supplements [9]. A recent study from France revealed that only 6.4% of women filled their prescription for folate supplements in the preconceptional period between 2006 and 2016, based on objective data from registries [39]. Even though over-the-counter supplements were not included, this low number may indicate that self-reported adherence to supplement recommendations, as used in most other studies, might be overestimated to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies point out that high consumption of folic acid may cause adverse health effects [ 58 ]. According to other authors dealing with neural tube defect prevention, the future will require balanced decisions in the scope of food fortification in all European countries [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neural tube defects are a group of birth defects which are related to morbidity, mortality and lifelong disability. It can be prevented by periconceptional intake of folic acid 17 . Myelomeningocele being the most frequent type of NTD, have an incidence rate of 0.20-0.40/1000 births/year in Canada and the USA 18 .…”
Section: Discussionmentioning
confidence: 99%